Migrant Shepherds: Opportunities and Challenges for Mediterranean Pastoralism - Michele Nori (Revue de Géographie Alpine)
The first results of the TRAMed research report on how pastoralism – an activity seemingly destined for oblivion, a memory of a recent past – shows interesting signs of resilience and important adaptive capacities. In several south European countries, foreign workers (shepherds who have emigrated from other Mediterranean countries) play an important role in this process because they provide skilled labour at a relatively low cost. Such migratory flows enable the pursuit, evolution and diversification of an activity increasingly acknowledged as essential to the preservation of the region’s natural and cultural heritage; and yet, it is one that Europeans are practising less and less.Engaging this workforce in the process of adapting and innovating the sector by integrating and empowering them provides the opportunity to help train the shepherds and the breeders of tomorrow. Without them, the Mediterranean is likely to lose some of its most valuable and increasingly rare guardians, as well as the sophisticated knowledge that is critical to managing such rich but fragile territories in the face of the major socio-political and ecological changes affecting the region.